2015
DOI: 10.1016/j.cej.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Removal of estrone (E1), 17β-estradiol (E2), and 17α-ethinylestradiol (EE2) from wastewater by liquid–liquid extraction

Abstract: With the recent wide spread concerns of the environmental and public health effects of endocrine disrupting chemicals (EDCs), it is becoming important to develop new techniques to remove these substances from wastewater. EDCs find their way to the environment mainly via effluents from WWTPs. They are often cited as moderately hydrophobic, hence they have tendency to distribute to organic solvents and can then be removed using liquid-liquid extraction (LLE) techniques. However, despite being a mature chemical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 46 publications
(44 reference statements)
1
22
0
1
Order By: Relevance
“…Similar effect of pH was also reported in the literature [36]. As weak acids, EDCs (pKas~ 10.5) remain non-ionised at pH <pKa [27,42] and dissociate to their base conjugates at aqueous pH >pKa. The deprotonation at high pHs of the EDCs increases their aqueous solubility (Table S2).…”
Section: Effect Of Ph On Edcs Adsorption On Pa6supporting
confidence: 83%
See 1 more Smart Citation
“…Similar effect of pH was also reported in the literature [36]. As weak acids, EDCs (pKas~ 10.5) remain non-ionised at pH <pKa [27,42] and dissociate to their base conjugates at aqueous pH >pKa. The deprotonation at high pHs of the EDCs increases their aqueous solubility (Table S2).…”
Section: Effect Of Ph On Edcs Adsorption On Pa6supporting
confidence: 83%
“…Several techniques used to remove and recover EDCs in water have extensively been studied [23][24][25][26]. For instance, we investigated the removal of estrogenic EDCs in water using liquidliquid extraction (LLE) and found that, at low pH than their pKa, they preferentially distribute to organic solvents because of their hydrophobicity while ozone-reactive LLE achieved almost instantaneous removal of the EDCs [27,28]. Ozonation has however produced oxidation products with endocrine disrupting character including 2OHE2 [12,28].…”
Section: Introductionmentioning
confidence: 99%
“…As evoked by Ward et al (Ward, Tizaoui et al 2004), there are two key factors that can enhance or hinder LLO process: the interfacial mass transfer and the effectiveness of promoted chemical reaction pathways. In a preliminary work, the mass transfer of the EDCs into D5 was investigated and their distribution coefficients were determined (Ben Fredj, Nobbs et al 2015). The results showed EDCs to distribute into D5…”
Section: Figure 4 Compares the Degradation Rates Of Edcs Achieved By mentioning
confidence: 99%
“…with diffrent distribution coefficients: E1 (K E1 =2.66) highly distributed in D5, followed by EE2 (K EE2 =1.67) and by E2 (K E2 =0.61) at pH 6 and at 20°C (Ben Fredj, Nobbs et al 2015).…”
Section: Figure 4 Compares the Degradation Rates Of Edcs Achieved By mentioning
confidence: 99%
“…The kinetic adsorption test was carried out by using EMIPs or ENIPs (20 mg) that were dispersed in the E1 aqueous solution (10 mL) and shaken at room temperature for different time (5,10,15,20,30,45,60,90, and 120 min), and then filtered. The supernatant was measured by HPLC and the adsorption capacity was calculated.…”
Section: Adsorption Testmentioning
confidence: 99%